Inhibitory Activities of Pyrazolo-Oxazine Heterocyclic Derivatives - Farghaly, Thoraya A.; Dawood, Kamal M. (Mini Reviews in Medicinal Chemistry, 2022)
Despite several reports and reviews addressing the biological significance of pyrazoles and oxazines, no comprehensive work on the pyrazolo oxazine fused ring system has been published so far. We report all biological evaluations on pyrazolo-oxazine derivatives in this mini-review to provide an avenue for medicinal and pharmacological researchers to conduct further in-depth exploration.
Keywords: anti-hepatitis (HCV)